GAMBARAN STATUS GIZI PADA MAHASISWA AKADEMI KEPERAWATAN RUMKIT TK.III MANADO - Wanantara, Made Ardika; Mayulu, Nelly; Onibala, Franly (e-NERS)
Abstract: One way to monitor the nutritional status of adults is by measuring body mass index. At present time has developed a body mass index chart adults (aged over 18 years) by using the index weight by height. The main purpose of this study is to reveal the nutritional status of students of the Academy of Nursing Rumkit Tk.III Manado. The method used in this research is descriptive method with cross sectional approach. The population in this study is the College Student Nursing Rumkit Tk.III Manado total sampling methods or sampling saturated totaling 265 people. This research was conducted at the campus of the Academy of Nursing Rumkit Tk.III Manado. The results says the respondents with a normal nutritional status as many as 213 people, respondents were underweight and nutritional status as many as 33 people, respondents with more weight nutritional status as many as 14 people and respondents with nutritional status obesity by 5 people. The conclusion of this study is the majority of respondents (80.4%) had normal nutritional status, nutritional status underweight (12.5%), nutritional status more weight (5.3%), and obesity (1.9%). Suggestion expected the Academy of Nursing Rumkit Tk.III Manado in this case more specifically on the student to be more attention to the nutritional importance keep maintaining the nutritional status of students. Keywords: Nutrient state, Students.     Abstrak: Salah satu cara untuk memantau status gizi orang dewasa ialah dengan mengukur indeks massa tubuh. Sekarang telah dikembangkan grafik indeks massa tubuh orang dewasa (umur diatas 18 tahun) dengan menggunakan indeks berat badan menurut tinggi badan. Tujuan penelitian ini adalah untuk mengetahui gambaran status gizi pada mahasiswa Akademi Keperawatan  Rumkit Tk.III Manado. Metode yang digunakan dalam penelitian ini adalah metode deskriptif dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah Mahasiswa Akademi Keperawatan Rumkit Tk.III Manado dengan metode pengambilan sampel  total sampling atau sampling jenuh yang berjumlah 265 orang. Penelitian ini dilaksanakan di Kampus Akademi Keperawatan Rumkit Tk.III Manado. Hasil penelitian menyebutkan responden dengan status gizi normal sebanyak 213 orang, responden dengan status gizi kurus sebanyak 33 orang, responden dengan status gizi berat badan lebih sebanyak 14 orang dan responden dengan status gizi obesitas sebanyak 5 orang. Kesimpulan dari penelitian ini adalah sebagian besar responden (80,4%) memiliki status gizi normal, status gizi kurus (12,5%), status gizi berat badan lebih (5,3%), dan obesitas (1,9%). Saran diharapkan pihak Akademi Keperawatan Rumkit Tk.III Manado dalam hal ini lebih khusus pada bagian gizi kemahasiswaan agar lebih memperhatikan pentingnya menjaga status gizi mahasiswa. Kata kunci: Status Gizi, Mahasiswa.